Caracterización de la población en el uso de las herramientas de prueba de algoritmos para el aprendizaje de los lenguajes de programación - Cortés Méndez, Jairo Augusto (UNIVERSIDAD ANTONIO NARIÑO, 2012)
One of the difficulties that have the students when they are in the process of learning of the computational logic is the one of being able to demonstrate as the abstraction of the real world in the solution of problems by means of the construction of a logical sequence of steps can be observed by means of the use of tools of test of algorithms. All the students easily do not acquire abilities and competitions in the identification of basic the computational structures for the resolution of problems. These students require greater practice by means of examples and exercises that allow to be modeling their logical structure him for the solution of problems. Therefore I analyze myself if influence exists or not of the tools of test of algorithms in the learning of the basic structures and of control of the programming languages. The problematic one that persists is the lack of tools in the education of the introductory courses to the programming languages and identification of educative necessities that they can be covered by means of the construction of a pedagogical and didactic tool like learning atmosphere of the structures of the programming languages, using a graphical language and of pseudo code in Spanish designed by the user. For the identification of the population and characterization I used and applied instruments that allowed measuring the attitudes and competitions with respect to the learning of the programming languages by means of the use of tools to prove algorithms.